A expansão da verticalização no bairro de Casa Caiada, Olinda/PE (1990 a 2015) - Santos, Michele Kely Moraes (2016)
This research aims to conduct a study of the vertical integration process in the Casa Caiada neighborhood, Olinda / PE, especially on the waterfront, on a timescale between the years 1990-2015, considering the main actors and subjects involved in this process. For such an analysis was performed of Casa Caiada neighborhood, which is located on the northern coast of the city of Olinda, considered both by real estate agents and the public power, a potential area for expansion of vertical integration because of its natural amenities. As regards the methodological aspect, they were adopted: a local scale and a historical and geographical perspective based on orality, which aims to provide qualitative interpretations of social-processes. In addition to the documentary information sources (books, newspapers, photographs) were also used oral testimony, considering the life histories and worldviews of people, social research subjects. The expansion of vertical integration in the Casa Caiada neighborhood expresses a process that is largely linked to the new context of modern society, characterized by appealing increasing the consumption, where everything seems to be making merchandise. New signs and symbolisms status and quality of life invade our day-to-day, influencing the pleasures and needs individual and collective needs. Modernity that installs in Olinda or Casa Caiada neighborhood from the economic point of view is not confirmed in the political sphere. While the city is of new real estate products, which represent more an appeal to the consumption of housing of the high-income strata have the permanence of social and environmental problems that slip in the political conservatism that both marks the Brazilian society. Thus, it is clear that the social production of urban space is an ongoing process where confront changes and maintenance. It is expected that the current revision of the Master Plan promotes changes for the better.